The Effectiveness of the Jigsaw Cooperative Learning Method in Improving Students’ Arabic Learning - Wahyuni, Nelsa; Falah, Mega Satria Nurul; Darwanto, Agus (Ahlussunnah: Journal of Islamic Education, 2026)
This study examines the effectiveness of the Jigsaw cooperative learning method in improving Arabic learning outcomes among Paket B students in a nonformal education program. The research was motivated by the relatively low level of achievement in Arabic learning, which was largely associated with teacher-centered instruction and limited student engagement during classroom activities. The research employed a pre-experimental one-group pretest–posttest design involving 24 students as research participants. The learning material was taken from Muhadatsah – Arabiyah Bayna Yadaik Jilid 1A, Bab 7 (Ad-Dirasah), while learning outcomes were measured using a 10-item multiple-choice test administered before and after the treatment. The instructional intervention was implemented through the Jigsaw model, emphasizing expert-group collaboration, peer explanation, responsibility sharing, and collective presentation. Data were analyzed descriptively through comparison of pretest and posttest scores and gain-score interpretation. The results indicate a substantial increase in students’ Arabic learning achievement after the implementation of the Jigsaw method, showing that cooperative interaction significantly enhances comprehension, learning participation, and students’ confidence in using Arabic expressions. The study strengthens empirical evidence on the relevance of cooperative learning for nonformal education contexts and highlights the potential of the Jigsaw model as an alternative pedagogical strategy to support meaningful and collaborative Arabic learning.